Investigating the reciprocal temporal relationships between tobacco consumption and psychological disorders for youth: an international review. Issue 6 (13th June 2022) - Stevenson, Jeremy; Miller, Caroline Louise; Martin, Kimberley; Mohammadi, Leila; Lawn, Sharon
Abstract : Objective: To investigate reciprocal temporal relationships between tobacco consumption and psychological disorders for youth. Design: Review Data sources: Five databases (PubMed, Embase, Scopus, CINAHL and PsycINFO) on 26 September 2019 and updated on 11 May 2021, indexing tobacco, mental illness and longitudinal. Study selection: Methods used consensus and multiple reviewers. Interventions: Cohort studies (n=49) examining tobacco and selected psychological disorders (depression, anxiety, bipolar, psychosis, borderline personality disorder) among youth, and systematic reviews (n=4) of these relationships met inclusion criteria. Primary and secondary outcome measures: Effect of tobacco on psychological disorders and effect of psychological disorders on tobacco. Data extraction and synthesis: Independent extraction by the first author and checked by final author. Joanna Briggs Institute Critical Appraisal Tools were used for all studies. Included studies had moderate-to-high appraisal scores. We synthesised findings using vote counting for effect direction and descriptive data. Results: Fifty-three studies were included in the review. Thirteen of 15 studies showed a positive effect direction of tobacco on depression (p<0.001). Six of 12 studies showed a positive effect direction of depression on tobacco (p=0.016). Six of eight studies showed a positive effect direction of tobacco on anxiety (p=0.016). Eleven of 18 studies showed a positive effect direction of anxiety on tobacco (p=0.003). No effect between tobacco and bipolar, or tobacco and psychosis was found. No studies examined tobacco and borderline personality disorder. Conclusions: Reciprocal relationships existed between tobacco and both depression and anxiety for youth, though causality is unconfirmed. No positive effect direction was found between tobacco and psychosis, perhaps because nicotine has conflicting effects on psychosis. For other relationships examined, evidence was weak because of low number of studies. More research to inform prevention and early intervention is needed. PROSPERO registration number: CRD42020150457.